Fabrication Issues of Sandwich-Like Flow Inserts for Circular Pipes. (17th November 2017) - Koehly, C.; Bühler, L.
Abstract: The dual-coolant lead lithium (DCLL) blanket in which the eutectic lead-lithium alloy is used as tritium breeder and coolant is a promising concept for applications in fusion power plants. The interaction of the moving electrically conducting liquid metal with the plasma-confining magnetic field induces electric currents and creates strong electromagnetic Lorentz forces opposing the flow. This may lead to high magnetohydrodynamic (MHD) pressure drops. Efficient cooling requires a sufficiently high flow velocity and, under these conditions, if currents find a shortcut through electrically conducting walls, the pressure drop will be very large. One way to reduce the MHD pressure drop in ducts is to decouple electrically the coolant flow from the load-carrying walls by insulating flow channel inserts (FCI). In order to demonstrate the capability of pressure drop reduction by FCIs in 3D MHD flow, a test section is currently being designed and manufactured for experiments in the MEKKA laboratory at the Karlsruhe Institute of Technology. The used FCIs are of sandwich-type with a ceramic layer protected from both sides by thin sheets of steel to prevent direct contact of the insulator with liquid metal. This technical note focuses on fabrication issues of sandwich-type flow channel inserts for circular pipes and shows methods and techniques for successful manufacturing.